2015
DOI: 10.1007/s13277-015-3580-2
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical significance of CUL4A in human prostate cancer

Abstract: Aberrant expression of the Cullin 4A (CUL4A) is found in many tumor types, but the functions and mechanism of CUL4A in prostate cancer (PCa) development and progression remain largely unknown. The aim of this study was to investigate the possible role of CUL4A in prostate tumorigenesis. Immunohistochemistry was used to examine CUL4A expression in human PCa tissues and BPH tissues. Cell proliferation was assessed by MTT, and migration and invasion were analyzed by Transwell and Matrigel assays after CUL4A knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…These genes include: transcription factor Dp-1 (TFDP1) , cullin 4A ( CUL4A) , and cell division cycle 16 ( CDC16) identified in hepatocellular carcinoma (HCC) [ 7 ], breast cancer [ 8 ], and lung cancer [ 9 ]; and insulin receptor substrate 2 ( IRS2) present in colorectal cancer [ 10 ]. CUL4A overexpression has been reported to be associated with migration, invasion, epithelial-mesenchymal transition and disease progression [ 11 13 ]. The role and frequency of gene CN alterations at 13q34 in iCCA has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These genes include: transcription factor Dp-1 (TFDP1) , cullin 4A ( CUL4A) , and cell division cycle 16 ( CDC16) identified in hepatocellular carcinoma (HCC) [ 7 ], breast cancer [ 8 ], and lung cancer [ 9 ]; and insulin receptor substrate 2 ( IRS2) present in colorectal cancer [ 10 ]. CUL4A overexpression has been reported to be associated with migration, invasion, epithelial-mesenchymal transition and disease progression [ 11 13 ]. The role and frequency of gene CN alterations at 13q34 in iCCA has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…35:111-116, doi 10.1007/s13277-013-1013 Jin, B., Dong, P., Li, K. et al (2014) Meta-analysis of the association between GSTT1 null genotype and risk of nasopharyngeal carcinoma in Chinese Tumor Biol. Jiang, Y., Sun, S., Liu, G. et al (2015) Nrdp1 inhibits metastasis of colorectal cancer cells by EGFR-signaling-dependent MMP7 modulation Tumor Biol. 36:1129-1133, doi 10.1007/ s13277-014-2726-y Zhang, Z., Yan, Z., Yuan, Z. et al (2015 Lin, ZY., Song, QQ., Chen, J. et al (2015) Local curative effect of MRI-guided radiofrequency ablation on small hepatocellular carcinoma Tumor Biol.…”
mentioning
confidence: 99%
“…Previous studies have shown that Cul4A is amplified in malignant pleural mesothelioma , breast , lung cancer and liver cancers . Overexpression of Cul4A has been reported in pituitary adenoma , prostate cancer and osteosarcoma . Cul4A overexpression is associated with tumorigenesis of lung cancer and hepatocellular carcinoma .…”
Section: Introductionmentioning
confidence: 98%